2016
DOI: 10.1016/j.midw.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Birth Satisfaction Scale/Birth Satisfaction Scale-Revised (BSS/BSS-R): A large scale United States planned home birth and birth centre survey

Abstract: Objective: To explore the prevalence of birth satisfaction for childbearing women planning to birth in their home or birth centers in the United States. Examining differences in birth satisfaction of the home and birth centers; and those who birthed in a hospital using the 30-item Birth Satisfaction Scale (BSS) and the 10-item Birth Satisfaction Scale-Revised (BSS-R).Study design: A quantitative survey using the BSS and BSS-R were employed.Additional demographic data were collected using electronic linkages (Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 16 publications
6
51
2
1
Order By: Relevance
“…The BSS-R has been validated and translated into Greek (Vardavaki, Hollins Martin, & Martin, 2015) and a United States (Barbosa-Leiker, Fleming, Hollins Martin, & Martin, 2015) version of the tool, with these studies suggesting excellent validity and reliability. The US version of the BSS-R has recently been used in a large-scale US study (Fleming et al, 2016) and a psychometric evaluation of the data from that study corroborated not only the excellent psychometric properties of the US version, but also its measurement robustness when comparing discrete sub-groups within the sample (C. R. Martin et al, 2016a). A comparison of UK and Greek BSS-R datasets has revealed the instrument to be both conceptually and statistically comparable (C.R.…”
Section: Contrasting Withmentioning
confidence: 80%
See 1 more Smart Citation
“…The BSS-R has been validated and translated into Greek (Vardavaki, Hollins Martin, & Martin, 2015) and a United States (Barbosa-Leiker, Fleming, Hollins Martin, & Martin, 2015) version of the tool, with these studies suggesting excellent validity and reliability. The US version of the BSS-R has recently been used in a large-scale US study (Fleming et al, 2016) and a psychometric evaluation of the data from that study corroborated not only the excellent psychometric properties of the US version, but also its measurement robustness when comparing discrete sub-groups within the sample (C. R. Martin et al, 2016a). A comparison of UK and Greek BSS-R datasets has revealed the instrument to be both conceptually and statistically comparable (C.R.…”
Section: Contrasting Withmentioning
confidence: 80%
“…A pertinent feature of Australian maternity care services are that they remain highly medicalised (Benoit, Zadoroznyj, Hallgrimsdottir, Treloar, & Taylor, 2010;Weaver, Clark, & Vernon, 2005) despite the strong movement led by government reforms towards midwifery-led models (Quinn, Noble, Seale, & Ward, 2013;Tracy et al, 2013;Tracy et al, 2014). However, the movement toward woman-centred care and choice has gathered some pace in Australia (Catling & Homer, 2016) and similar to both the UK and the US (Fleming et al, 2016; C. J. The BSS-R would appear to be ideally suited as the measure of choice within this context, however an Australian version of the BSS-R has to date, yet to be developed and psychometrically evaluated.…”
Section: Pregnancy and Childbirth Standard Set (International Consortmentioning
confidence: 99%
“…The revised version of the scale is a more robust version. They have been used in research [97–99] and further cultural translation and validation has been made in Greece and the US [79, 80, 100]. The Early Labour Experience Questionnaire/ELEQ [47]Janssen & Desmarais (2013)USATo measure women’s experiences with their early labour care.Developed to measure women’s experience and evaluate care given in the latent and early phase of labour [47, 101].…”
Section: Resultsmentioning
confidence: 99%
“…As we have stated before, expectations play an important role on the overall satisfaction, since women who planned to give birth at home or a birth center but ended up in the hospital tended to score lower on satisfaction tests (44). Studies developed in Belgium and Sweden also showed that women who needed to be transferred to a hospital tended to describe negatively the overall experience and emotional aspects of it (45).…”
Section: 5% Of Multiparous)mentioning
confidence: 68%
“…When it comes to the actual satisfaction of the process it becomes clear that it relies not only on the chosen setting, but also in the expectations that the women may have developed towards the process. However, S. Fleming et al (44) did nd that satisfaction was higher for women who had both planned to deliver in a home or a birth center, and who had actually delivered in a home or a birth center. These ndings were assessed using both the Birth satisfaction scale (BSS) and a shorter version on it, the Birth satisfaction scale revised (BSS-R).…”
Section: 5% Of Multiparous)mentioning
confidence: 98%